PERSPEKTIF HUKUM ISLAM MENGENAI MEKANISME MANIPULASI PASAR DALAM TRANSAKSI SAHAM DI PASAR MODAL - Sawaluddin Siregar (Yurisprudentia: Jurnal Hukum Ekonomi, 2017)
The market manipulation of stock transactions in the capital market is done by the conspiracy of several parties who engineered the balance of the selling offer and the buying demand of shares to influence the movement of stock transactions, in order to create a false or misleading image in the capital market, so that investors mistakenly take investment decisions, and the manipulators benefit . Market manipulation in stock transactions in capital markets is a practice that is prohibited in Articles 91 and 92 of Law No. 8 of 1995 on Capital Markets. Market manipulation is also prohibited in Islamic law, because it is categorized as bale an-najsy (false demand) and ihtikar (false supply), as affirmed in Article 5 paragraph 2 Fatwa DSN-MUI No. 40 / DSN-MUI / X / 2003.